2005
DOI: 10.1007/s00455-005-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Esophageal Motility in Patients with Solid Dysphagia and Mixed Dysphagia

Abstract: It is unclear whether there is any difference in esophageal motor abnormalities between patients complaining of dysphagia for solids or both solids and liquids. The aim of this study was to determine any difference in the manometric findings between patients with dysphagia for solids and those with mixed dysphagia. Manometric tracings were performed in 200 consecutive patients (66 M, 134 F; mean age = 51 years) with nonobstructive dysphagia. Ambulatory pH studies were performed in all patients. Subjects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…They found that GERD was a risk factor for dysphagia as well as odynophagia; indeed, intermittent dysphagia and odynophagia were independently associated with GERD symptoms (OR: 2.96, 95% CI: 1.76-4.98; OR: 3.41, 95% CI: 1.16-10.04, respectively), but dysphagia was also associated with depression and anxiety. However, esophageal motility studies have shown that patients with solid dysphagia are more likely to have GERD than those with mixed dysphagia [21] .…”
Section: Stricturesmentioning
confidence: 99%
“…They found that GERD was a risk factor for dysphagia as well as odynophagia; indeed, intermittent dysphagia and odynophagia were independently associated with GERD symptoms (OR: 2.96, 95% CI: 1.76-4.98; OR: 3.41, 95% CI: 1.16-10.04, respectively), but dysphagia was also associated with depression and anxiety. However, esophageal motility studies have shown that patients with solid dysphagia are more likely to have GERD than those with mixed dysphagia [21] .…”
Section: Stricturesmentioning
confidence: 99%
“…Furthermore, stroke and cancer of the head and neck may also result in dysphagia in response to morphologic changes or treatment effects [7]. Other physical disorders linked to dysphagia include hypertension and gastroesophageal reflux disease, which can cause scarring of the esophagus [8][9][10].…”
Section: The Physiology Of Swallowingmentioning
confidence: 99%
“…Patients presenting alterations of the esophageal phase should be investigated through more specific tests, such as endoscopy, esophageal manometry and esophageal pH metry, because the VFSS is a screening tool that can aid in selection of other tests and disclose diagnosis of esophageal disorders (1,2,11,16,18) . Importantly, the screening of the esophageal phase of swallowing through videofluoroscopy is of short duration and can be easily carried out.…”
Section: Discussionmentioning
confidence: 99%